PEER-MENTORING ROLE IN MENTORSHIP PROGRAM IMPLEMENTATION FOR MEDICAL STUDENT - Harahap, Iqbal Alaudilah; Noija, Stazia; Tentua, Vebiyanti (Universitas Gadjah Mada, 2023)
Background: The first year as a medical student is a transition phase and adapts from senior high school to medical student that focuses on student center learning. Many students can't adapt in first year as a medical student to affect academic performance. It can make self-esteem and motivation decrease, frustration, stress, avoid talking to others, avoid faculty support, and potential fail in the future. Several medical faculty implement peer-mentoring to assist students to solve this problem with increasing motivation, self-esteem and personal development. This study aims to identify mentorship program implementation at Medical Faculty of Pattimura University.Methods: This study was a type of descriptive observational study used primary data with a cross-sectional approach. The sample of this study was first year students at Medical Faculty of Pattimura University used total sampling.Results: The result of this study was taken 202 respondents from 205 first year students who joined the peer-mentoring program “MENISCUS” showed frequency of the program is 2–4 meetings on duration > 60 minutes with 3 mentoring method combination and be held online (virtual meeting). In addition, based on mentees feedback showed that overall this program helps in personal, skills and professional development.Conclusion: Mentorship program implementation at Medical Faculty of Pattimura University showed effectiveness and provided benefits in personal, skills, and professional development.